Student responses to internet based delivery programmes at institute of business and management studies - Ong, Eugenie (Universiti Malaysia Sarawak (UNIMAS), 2002)
The purpose of this study was to gather and analyse feedback from undergraduate and masters students enrolled in University of Southern Queensland (USQ) programmes at IBMS during the third semester (Nove 01 to Jan 02) regarding the use of the USQConnect and USQOnline in their studies